2010
DOI: 10.1111/j.1365-2656.2010.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

The spatial scaling of habitat selection by African elephants

Abstract: Summary1. Understanding and accurately predicting the spatial patterns of habitat use by organisms is important for ecological research, biodiversity conservation and ecosystem management. However, this understanding is complicated by the effects of spatial scale, because the scale of analysis affects the quantification of species-environment relationships. 2. We therefore assessed the influence of environmental context (i.e. the characteristics of the landscape surrounding a site), varied over a large range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 57 publications
3
97
0
Order By: Relevance
“…Our approach of predicting animal numbers on the basis of food distributions, known metabolic cost functions and interference-based functional responses should be applicable to other systems. For example, an understanding of the ecological underpinning of the distribution of large herbivores in, for example, the Serengeti or Kruger National Park [64,65] is based on correlative exercises (plotting presence on indirect measures of habitat suitability) rather than the kind of thoroughly understood mechanistic reasoning presented here. There is also a substantial body of work using large-scale surveys of marine mammals to model their habitat selection.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach of predicting animal numbers on the basis of food distributions, known metabolic cost functions and interference-based functional responses should be applicable to other systems. For example, an understanding of the ecological underpinning of the distribution of large herbivores in, for example, the Serengeti or Kruger National Park [64,65] is based on correlative exercises (plotting presence on indirect measures of habitat suitability) rather than the kind of thoroughly understood mechanistic reasoning presented here. There is also a substantial body of work using large-scale surveys of marine mammals to model their habitat selection.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors (Johnson et al 2002, Fryxell et al 2008 have demonstrated that differences in selection patterns between scales may arise from different movement modes (and different objectives, such as foraging or traveling) at different scales. Other authors aim to find a characteristic scale at which selection is most pronounced (Holland et al 2010, de Knegt et al 2011. Regardless of scale, however, animals select habitats high in forage biomass and low in risk, when possible (Rettie andMessier 2000, Owen-Smith et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Initial vegetation biomass density per cell was calculated by combining these imagery-and field-based maps on tree, shrub, and herbaceous cover ( Fig. 1; Kiker 1998, De Knegt et al 2011, vegetation type, mean tree, shrub, and herbaceous root biomass, height data, and on an initial sizeclass distribution for trees. Precipitation and more detailed information about radiation, CO 2 concentration, wind speed, minimum and maximum temperature, and humidity (Coughenour 1993, Boone 2007 were obtained from a series of weather stations.…”
Section: Modelmentioning
confidence: 99%
“…To manipulate the impact of elephants on their habitat, the construction or closure of artificial water points (WPs) is considered to be a suitable strategy (Smit et al 2007a, as surface water is a key driver in elephant distribution and population dynamics (Chamaille´-Jammes et al 2007a, De Knegt et al 2011. Due to the construction of WPs, elephants may range into areas that were previously inaccessible to them or spend longer periods in areas where they would only have ranged when natural water was available (Loarie et al 2009, Smit andGrant 2009); elephant home range sizes may decrease in both the dry and the wet season (de Beer andVan Aarde 2008, Van Aarde et al 2008); and elephant densities may increase locally, since young animals are, predominately, susceptible to droughts (Chamaille´-Jammes et al 2007b, Van Aarde andJackson 2007).…”
Section: Introductionmentioning
confidence: 99%